A Comparative Clinical Study of Virechana Karma and Lekhana Basti in the Management of Sthaulya - Tejal Khunt, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
A Comparative Clinical Study of Virechana Karma and Lekhana Basti in the Management of Sthaulya